Community health improvement plan: Study protocol for Kansas City's intervention and implementation evaluation - Joseph S. Lightner; Lana McKinney; Kate Hoppe; Nancy Ziegler; Kelsey Gardiner; Scott Clardy; Tyler Prochnow; Vicki Collie-Akers (Elsevier, 2022)
Objectives: Community health improvement plans (CHIPs) are foundational public health practice, yet no studies have been conducted to understand implementation of these plans. This evaluation study of the Kansas City CHIP aims to 1) identify implementation strategies used in the CHIP, 2) assess changes in implementation, service, and client outcomes, 3) assess contextual factors associated with implementation, and 4) understand social networks of coalitions who implement the Kansas City CHIP. Study design: This study protocol uses a unique, mixed methods approach to evaluating process and outcomes of the Kansas City CHIP. This study is supported by Proctor's Model of Implementation, RE-AIM (reach, effectiveness, adoption, implementation, maintenance), and the practical, robust implementation and sustainability model (PRISM). Methods: Staff and community members involved in implementing the Kansas City, Missouri CHIP will be invited to participate in an annual online survey, a series of focus groups, and quarterly implementation logs to assess implementation and sustainability. Results: RE-AIM and PRISM constructs are the primary and secondary outcomes of interest. Results of this study will be available from the first year of implementation in 2023, with future results provided annually. Conclusions: This project will fill a much-needed gap in the literature by understanding how large-scale coalitions implement projects that aim to improve population health and health equity. CHIPs have the potential to improve population health, yet few studies have been conducted on CHIPs, with no studies to date assessing outcomes. To support effective implementation and sustainability as well as improve public health outcomes, researchers need to evaluate CHIPs and develop models of implementation that can quickly be integrated into practice to improve populations' health.